Understanding Zora Neale Hurston's Their Eyes Were Watching God - Tatjana Vukelić (Acta Neophilologica, 2007)
The work of Zora Neale Hurston, in particular, the novel Their Eyes Were Watching God, has been the object of more than a decade of critical attention. But, in addition to the critical consideration of Hurston's writings, her work has received the level of institutional support necessary for Hurston to enter the American literary mainstream. The article addresses the issue of black women literary tradition and the search for freedom and identity in the white American social and cultural environment.